1987
DOI: 10.1136/hrt.58.6.592
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vagal heart rate control in coronary artery disease.

Abstract: SUMMARY Heart rate variation in deep breathing, a sensitive non-invasive measure of cardiac parasympathetic activity, was measured in 63 patients with coronary artery disease, in 22 patients with atypical chest pain, and in 20 healthy symptom free volunteers. There was significantly less heart rate variation in deep breathing in the patients with coronary artery disease than in the healthy subjects. Twenty patients (32%) with coronary artery disease had lower than normal variation in heart rate. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 31 publications
5
46
0
Order By: Relevance
“…However, it must be remembered that autonomic neuropathy cannot be diagnosed on the basis of one abnormal cardiovascular reflex. Furthermore, myocardial infarction is associated with autonomic dysfunction (35)(36)(37)(38), which may cause similar alterations in Valsalva ratio as diabetic autonomic neuropathy (35). Therefore, in a critical interpretation the findings described by Niakan et al may only reflect the often disregarded effect of myocardial infarction on autonomic nervous function.…”
Section: Diabetic Autonomic Neuropathy and Silentmentioning
confidence: 86%
See 1 more Smart Citation
“…However, it must be remembered that autonomic neuropathy cannot be diagnosed on the basis of one abnormal cardiovascular reflex. Furthermore, myocardial infarction is associated with autonomic dysfunction (35)(36)(37)(38), which may cause similar alterations in Valsalva ratio as diabetic autonomic neuropathy (35). Therefore, in a critical interpretation the findings described by Niakan et al may only reflect the often disregarded effect of myocardial infarction on autonomic nervous function.…”
Section: Diabetic Autonomic Neuropathy and Silentmentioning
confidence: 86%
“…One limitation on any clinical evaluation of the association of autonomic neuropathy with the lack of cardiac pain is that this part of autonomic function is difficult to assess. The heartrate responses used for the conventional diagnosis of autonomic neuropathy mainly reflect the integrity of cardiac parasympathetic activity, and an additional problem with the heart-rate tests is the confounding effect of coronary artery disease and myocardial infarction (35)(36)(37)(38)40,41). Preliminary studies suggest that the distribution of myocardial sympathetic nerves may be assessed with radiolabeled metaiodobenzylguanidine (43).…”
Section: Diabetic Autonomic Neuropathy and Silentmentioning
confidence: 99%
“…1,2 In patients with CAD or congestive heart failure (CHF) or both, the short-term heart rate variability (HRV) is significantly lower in those with inducible ventricular tachycardia than in those without clinical or electrocardiographic (ECG) evidence of ventricular tachycardia; and the probability of developing sudden death increases substantially when short-term HRV decreases below 50 ms. 3 It has also been shown that the very-low-frequency power (VLFP) of HRV is an independent risk predictor in patients with CHF. 4 In addition, vagal enhancement has been shown to have an antiarrhythmic effect in acute ischemic animal models, 5,6 and can terminate ventricular tachycardia in humans.…”
mentioning
confidence: 99%
“…Reduced parasympathetic activity in these patients have been found to be associated with malign ventricular arrhythmias and sudden cardiac death. Patients who have marked autonomic dysfunction leading to reduced HRV are at increased risk of premature death (8)(9)(10)(11)(12)(13)(14). Hypoxia in chronic respiratory disease can also induce autonomic abnormalities leading to reduced HRV (25).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal cardiac autonomic function was identified with HRV in left ventricular dysfunction, diabetes mellitus and after myocardial infarction (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%